Monetization of Politics and Elections in Fourth Republican Nigeria: Implications for Sustainable Democratic Governance. - Okunloye, Rotimi William (NIU Journal of Humanities, 2018)
Politics in democratic political system thrives on popular political participation in free, fair, period and credible intra-party and general elections. These democratic norms have been greatly associated with older democracies where a greater majority of citizens as politicians and electorates have imbibed the participant or civic democratic culture. However, in relatively new or emerging democracies such as Nigeria, citizens imbibed more of parochial or subject political culture. While politicians perceived and play zero-sum politics and use all means, including offering of material inducements, use of force and other unconstitutional means in electoral politics. These explains why the Independent National Electoral Commission (INEC), reported the nullification of 117 election results after the 2015 general elections in Nigeria. The recurrence of nullification of results of general election and even intra-party elections by election tribunals and courts are sufficient empirical evidence of low level awareness of the unfolding trends of monetisation of politics or electoral corruption in Nigeria. Therefore, this paper examines the rising trend of monetisation of politics and elections in the fourth Republic. The paper identifies the characteristic traits and incidences of monetisation of politics in Nigeria and its players or political actors. The paper further highlighted the perception of monetised politics, the factors associated with its observable trend in fourth republican Nigeria, its implications for good governance and sustainable democracy in Nigeria. Finally, the paper proffers solutions for curtailing the dysfunctional trends in Nigeria politics to ensure sustainable democratic governance in the fourth republican Nigeria.